Pola Interaksi Masyarakat Pasca Konversi Agama di Desa Lokapaksa Kecamatan Seririt Kabupaten Buleleng - Ni Made, Yunitha Asri Diantary; Sunampan Putra, I Wayan (Kamaya: Jurnal Ilmu Agama, 2023)
This research is one of the studies that focuses on patterns of community interaction after religious conversions in Lokapaksa Village, Seririt District, Buleleng Regency. The reason for conducting this research was due to religious conversions that did not cause conflict during post-religious conversions. People who convert to religion can actually be accepted by the previous religious community. The purpose of this study is to explain the pattern of community interaction post-religious conversion in Lokapaksa village. This type of research is qualitative research with primary and secondary data. Collecting data by observation, interviews, documentation, and literature study. Then the data is analyzed and presented. The data obtained is that after the conversion of religion the people of Lokapaksa village show an associative pattern of interaction. The interactions that occur are influenced by several things such as imitation, suggestion, identification and sympathy. The basis of the pattern of community interaction is the philosophy of Tri Hita Karana. Based on these data, it can be concluded that the conversion that occurred did not lead to conflict but the community could live in harmony.